Age-specific prognostication after out-of-hospital cardiac arrest – The ethical dilemma between 'life-sustaining treatment' and 'the right to die' in the elderly. Issue 2 (March 2017) - Sulzgruber, Patrick; Sterz, Fritz; Poppe, Michael; Schober, Andreas; Lobmeyr, Elisabeth; Datler, Philip; Keferböck, Markus; Zeiner, Sebastian; Nürnberger, Alexander; Hubner, Pia; Stratil, Peter; Wallmueller, Christian; et al.
Background: While prognostic values on survival after out-of-hospital cardiac arrest have been well investigated, less attention has been paid to their age-specific relevance. Therefore, we aimed to identify suitable age-specific early prognostication in elderly patients suffering out-of-hospital cardiac arrest in order to reduce the burden of unnecessary treatment and harm. Methods: In a prospective population-based observational trial on individuals suffering out-of-hospital cardiac arrest, a total of 2223 patients receiving resuscitation attempts by the local emergency medical service in Vienna, Austria, were enrolled. Patients were stratified according to age as follows: young and middle-aged individuals (<65 years), young old individuals (65–74 years), old individuals (75–84 years) and very old individuals (>85 years). Results: There was an increasing rate of 30-day mortality (+21.8%, p  < 0.001) and unfavourable neurological outcome (+18.8%, p  < 0.001) with increasing age among age groups. Established predictive variables lost their prognostic potential with increasing age, even after adjusting for potential confounders. Independently, an initially shockable electrocardiogram proved to be directly associated with survival, with an adjusted hazard ratio (HR) of 2.04 (95% confidence interval (CI) 1.89–2.38, p  = 0.003) for >85-year-olds. Frailty was directly associated with mortality (HR 1.22, 95% CI 1.01–1.51, p  = 0.049), showing a 30-day survival of 5.6% and a favourable neurological outcome of 1.1% among elderly individuals. Conclusion: An initially shockable electrocardiogram proved to be a suitable tool for risk assessment and decision making in order to predict a successful outcome in elderly victims of out-of-hospital cardiac arrest. However, the outcomes of elderly patients seemed to be exceptionally poor in frail individuals and need to be considered in order to reduce unnecessary treatment decisions.